Pendekatan Cognitive Behavior Therapy untuk Meningkatkan Self-Esteem pada Remaja dengan Pengalaman Perceraian Orang Tua - Rani, Cut Athika; Hapsari, Indri (Universitas Muhammadiyah Metro, 2025)
Adolescence is a transitional period filled with challenges and opportunities for cognitive, emotional, and social development. One crucial aspect influencing adolescent well-being is self-esteem, an individual's evaluation of their worth and value. Low self-esteem is often associated with cognitive distortions that can affect adolescents' emotions and behaviors, leading to anxiety, depression, and maladaptive behaviors. This study explores the effectiveness of Cognitive Behavioral Therapy (CBT) in enhancing self-esteem among adolescents. CBT is an evidence-based psychotherapy approach that assists individuals in identifying and transforming maladaptive negative thought patterns into more realistic and adaptive ones. This research employs a case study method involving a 16-year-old adolescent with low self-esteem resulting from cognitive distortions about herself and her environment. The CBT intervention was conducted over six sessions, including psychoeducation, monitoring of thoughts and emotions, identification of cognitive distortions, and the development of new cognitive and behavioral skills. The results indicate a significant increase in the participant's self-esteem scores, measured using the Self-Perception Profile for Adolescents (SPPA) before and after the intervention. These findings suggest that CBT can be an effective intervention for enhancing adolescent self-esteem by equipping them with skills to manage emotions, alter negative thinking, and improve interpersonal relationships adaptively.